CONTINUOUS MONITORING OF LACTATE AND GLUCOSE DURING THE INTEGRAL SURGICAL MANAGEMENT OF ACQUIRED COMBINED HEART VALVULAR DISEASES AND ISCHEMIC HEART DISEASE - P. I. Len'kin; A. A. Smyotkin; A. Khusseyn; A. I. Len'kin; K. V. Paromov; A. A. Ushakov; M. A. Krygina; M. Yu. Kirov (Вестник анестезиологии и реаниматологии, 2017)
Lactate and glucose of the venous blood were continuously monitored using the Eirus system for intravascular microdialysis with 20 patients operated for complex non-heritable valvular heart disease and ischemic heart disease. The lactate and glucose concentrations, measured by microdialysis techniques, were correlated to the values of arterial blood (rho = 0.917, p < 0.0001 for lactate and rho = 0.693, p < 0.0001 for glucose, respectively). According to the Bland-Altman test results the mean difference between the values measured with Eirus system and that in arterial blood gases made 0.09 ± 1.1 mmol/L for lactate and -0.1 ± 4.65 mmol/L (M ± 1.96 SD) for glucose, correspondingly. Thus, the technique of intravascular microdialysis allows with acceptable accuracy continuous monitoring of lactate and glucose concentrations in median vein under combined high-risk cardiac surgery and timely diagnostics of the values variation in the perioperative period.